Rapid-synthesis of zeolite T via sonochemical-assisted hydrothermal growth method - Jusoh, N. (Elsevier B.V., 2017)
Sonochemical-assisted method has been identified as one of the potential pre-treatment methods which could reduce the formation duration of zeolite as well as other microporous and mesoporous materials. In the present work, zeolite T was synthesized via sonochemical-assisted pre-treatment prior to hydrothermal growth. The durations for sonochemical-assisted pre-treatment were varied from 30 min to 90 min. Meanwhile, the hydrothermal growth durations were ranged from 0.5 to 3 days. The physicochemical properties of the resulting samples were characterized using XRD, FESEM, FTIR and BET. As verified by XRD, the samples synthesized via hydrothermal growth durations of 1, 2 and 3 days and sonochemical-assisted pre-treatment durations of 60 min and 90 min demonstrated zeolite T structure. The samples which underwent sonochemical-assisted pre-treatment duration of 60 min yielded higher crystallinity with negligible change of zeolite T morphology. Overall, the lengthy synthesis duration of zeolite T has been successfully reduced from 7 days to 1 day by applying sonochemical-assisted pre-treatment of 60 min, while synthesis duration of 0.5 days via sonochemical-assisted pre-treatment of 60 min was not sufficient to produce zeolite T structure. © 2016 Published by Elsevier B.V.